2010
DOI: 10.1164/rccm.200911-1737oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolactin on TSC2-Null Eker Rat Cells and in Pulmonary Lymphangioleiomyomatosis

Abstract: Rationale: Lymphangioleiomyomatosis, a cystic lung disease of women, is characterized by proliferation of smooth muscle-like lymphangioleiomyomatosis cells, which possess mutations in the tuberous sclerosis complex genes, TSC1/TSC2. Growth factors involved in lymphangioleiomyomatosis cell proliferation are unknown. Prolactin, an important reproductive hormone in women, is known to promote cell proliferation and survival in other tissues. Objectives: To determine the role of prolactin in signaling and prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Regulation of the apoptotic potential of LAM cells is context-dependent and intimately related to met- abolic reprogramming and the nature of mitogenic stimuli. A variety of factors are likely to contribute to the proliferation of LAM cells, including β-catenin, which is activated in LAM (84)(85)(86), associated with upregulation of cyclin D1 (84), and contributes to LAM cell invasiveness (87); HMGA2, an architectural transcription factor that is misexpressed in a number of mesenchymal neoplasms (88); Polo-like kinase-1 (PLK1) (89) and PLK2 (90), which interact directly with TSC1 in a cell cycle-dependent manner; cyclin-dependent kinase inhibitor p27, which is mislocalized to the cytoplasm in TSC-deficient cells (91,92); and prolactin, a hormone and smooth muscle mitogen that is elevated in the serum of patients with LAM (93). A better understanding of these apoptotic and proliferative factors could lead to clearly targetable nodes.…”
Section: Pathways Affecting Proliferation and Survival Of Lam Cells: mentioning
confidence: 99%
“…Regulation of the apoptotic potential of LAM cells is context-dependent and intimately related to met- abolic reprogramming and the nature of mitogenic stimuli. A variety of factors are likely to contribute to the proliferation of LAM cells, including β-catenin, which is activated in LAM (84)(85)(86), associated with upregulation of cyclin D1 (84), and contributes to LAM cell invasiveness (87); HMGA2, an architectural transcription factor that is misexpressed in a number of mesenchymal neoplasms (88); Polo-like kinase-1 (PLK1) (89) and PLK2 (90), which interact directly with TSC1 in a cell cycle-dependent manner; cyclin-dependent kinase inhibitor p27, which is mislocalized to the cytoplasm in TSC-deficient cells (91,92); and prolactin, a hormone and smooth muscle mitogen that is elevated in the serum of patients with LAM (93). A better understanding of these apoptotic and proliferative factors could lead to clearly targetable nodes.…”
Section: Pathways Affecting Proliferation and Survival Of Lam Cells: mentioning
confidence: 99%
“…A number of known LAM serum biomarkers were identified in the LAM CORE secretome including VEGFD (FIGF), MMP2, and CTSK (Ferri et al, 2004;Seyama et al, 2006). The expression of PRLR (prolactin receptor, also known as Secreted Prolactin Binding Protein), a newly predicted serum biomarker, is induced by ESR1 and PGR, and is capable of activating PI3K/AKT, ERK1/2 and TP53 signaling (Alkharusi et al, 2016;Terasaki et al, 2010). Genes encoding extracellular matrix associated proteins (i.e., collagen, glycosaminoglycans, proteoglycans, and endopeptidases) were the most enriched components in the LAM cell secretome and were associated with diverse LAM relevant functions including cell migration, angiogenesis, growth factor and estrogen responsiveness, and WNT, PI3K/AKT, P53 signaling pathways (Figure 4a).…”
Section: The Lam Core Secretome Predicted By Scrna-seqmentioning
confidence: 99%
“…may provide growth advantages to LAM cells. LAM CORE cells from LAM lungs expressed a unique panel of signature genes expressed in uterine LAM cells and in normal human and mouse uterus but not in normal human lung.LAM CORE cells and normal myometrial cells shared transcriptomic similarity which are regulated by female sex hormones, including estrogen, progesterone and prolactin receptorsTerasaki et al, 2010). scRNA-seq analysis of normal human and mouse uterine cells demonstrated a close relationship of LAM CORE signatures with uterine myocytes.…”
mentioning
confidence: 92%
“…[103] and references therein). A single recent study [104] suggested that PRL signaling could also promote LAM disease based on: i) the association of elevated PRL levels with disease progression in patients; ii) elevated PRL and PRLR expression (mRNA and immunoreactivity) in LAM lesions compared with vascular smooth muscle cells in the same region of the tissue; and iii) increased PRLR expression, activation of PRLR signaling pathways and PRL-induced proliferation of cells lacking tuberous sclerosis complex 2 gene.…”
Section: Lymphangioleiomyomatosismentioning
confidence: 99%